Effectiveness of character and style in communicating myths of origin: A critical analysis of Tigania Community of Kenya - Rukunga, Mwamukui Priscila; Ndege, Speranza (Research Journal in Advanced Humanities, 2020)
Characterization in a work of art comprises the persons through whom the writer speaks to his audience. Characters play a vital role in literature as they control the plot of the story, bring out themes and arouse and sustain interest. Forster (1972) asserts that the importance of characterization is anchored on the fact that a writer is able to appeal to the intelligence and imagination of the reader. This paper examines six myths of origin from the Tigania Community. These myths are: The Origin of Death, Red-Thigh Woman, (Ngirani), Domestication of Animals, 'Gichiaro', Naming Patterns and Rain and Thunderstorms. These reveal the deep-rooted cultural subversion of the female gender and there seems no hope of unwarping the woman from the intricate web that culture has constructed for her. Characterization and style have been artistically interwoven in the creation of the myths. Chapman (1973) stipulates that in a literary work, language is conscious in formation and that it is a medium not only for communication or expression but for effect. This paper exposes a myriad of challenges assailing the female gender in the Tigania Community, whose patrilineal set up is deeply entrenched, this woman had desperately resigned to her fate.